FORMATION OF COGNITIVE FLEXIBILITY AND METACOGNITIVE SKILLS - Makhmarizayev Khurshid Otaqulovich (Bright Mind Publishing, 2025)
This article is devoted to the theoretical and methodological foundations of the development of cognitive flexibility and metacognitive skills in the professional training of future teachers. The complexity of the digital educational environment (information overload, hypertext, artificial intelligence integration) is analyzed, and the need for a high level of mental flexibility and effective self-management in these conditions is substantiated. The study proposes specific mechanisms for the formation of these competencies - problem-based learning (PBL), interactive methods using reflective e-portfolios and virtual simulations.
Keywords: Future teachers, Cognitive flexibility, Metacognitive skills, Digital learning environment, PBL, Reflection.